Aplikasi Agenda Surat Keluar dan Surat Masuk Berbasis Filing System - Wiwin Susanty; Fikri Rahman; Taqwan Thamrin (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2021)
This study aims to facilitate the organizers or staff or administrative staff to make an efficient and effective schedule. The benefit of this research is that it can improve the ease of scheduling and minimize problems for organizers in scheduling activities. This research method uses a Filing System which is an indicator of looking for letters based on the calendar, subject, letter number, and others when the letter is needed or needed. The data collection technique uses an approach technique or commonly called a qualitative technique, namely by means of observation to ensure that the company still performs scheduling activities manually. Then conducted interviews with the authorities in the correspondence section. The research location is at the Department of Culture and Sports of Bandar Lampung City. The result of this research is that if the organizer does the scheduling, it can save time, energy, and storage. because everything is done computerized.